Knowledge Sharing among Students of Universiti Utara Malaysia (UUM) - Rosnani, Daud (2010)
This study attempts to identify the factors that promote or encourage knowledge sharing activities among the University Utara Malaysia (UUM) students. Theory of Social Capital has been used as the indicator to knowledge sharing. The first objective of the study is to examine the relationship among explicit knowledge, tacit knowledge, trust, leadership and opportunity to share with knowledge sharing. Whereas the second objective is to find out whether there is a difference between local students vs. international student on knowledge sharing practice. A total of 300 questionnaires have been distributed to the master students from College of Business (COB). However, only 246 of them were returned and usable for analysis. Standard or simultaneous regression analysis is performed to test the hypotheses of the study. The result indicates that only two of contextual factors are positively significant to knowledge sharing while the other three of contextual factors are not. The findings are discussed and recommendations for the future research have also been addressed.